Measures of variability : range, sum of squares, variance & standard deviation. (Statistics for psychology, 2017)
In this final installment in his series on statistics for psychology, Professor Daniel Little offers a reference guide and glossary of concepts used throughout. He focuses on identifying and explaining the factors that define distribution variability.